The Development of Literacy-Based Land Minister Learning Media For Pancasila Education of Class IV Students Of Sdn 15 Koto Baru Dharmasraya - Asmaryadi, Ilham; Hader, Antik Estika; Fadila, Salza (The Future of Education Journal, 2024)
Literacy understanding has evolved significantly from mere reading and writing skills to encompass comprehension and use of technology. In the digital age, literacy now includes not only reading and writing but also speaking, understanding, and utilizing technology. These advanced literacy skills are crucial for addressing globalization challenges and enhancing social, cultural, and economic progress. Individuals with limited literacy skills may struggle to maximize their potential. To help students become better readers, one strategy employed is a 15-minute reading activity before lessons begin. Research applying the Research and Development (R&D) methodology and the ADDIE model, which includes five stages—analysis, design, development, implementation, and evaluation—shows that literacy-based learning media, such as "Candy Land," is highly effective. Evaluation results indicate that 85% of students achieved satisfactory learning outcomes, while 15% did not. This effectiveness demonstrates that literacy-based learning media can enhance student learning outcomes, with an average completion rate of 85%, supporting the use of this method in the learning process to achieve educational goals